Exploring the intersection of epigenetics, DNA repair, and immunology from studies of ICF syndrome, an inborn error of immunity - Unoki, Motoko (Frontiers in Immunology, 2024)
Immunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome, a rare autosomal recessive disorder, manifests with hypoglobulinemia and chromosomal instability accompanied by DNA hypomethylation. Variants in the DNMT3B, ZBTB24, CDCA7, or HELLS genes underlie its etiology. Activated lymphocytes from patients often display distinctive multiradial chromosomes fused via pericentromeric regions. Recent studies have provided deeper insights into how variants in ICFrelated proteins cause DNA hypomethylation and chromosome instability. However, the understanding of the molecular pathogenesis underlying immunodeficiency is still in its nascent stages. In the past half-decade, the roles of CDCA7, HELLS, and ZBTB24 in classical non-homologous end joining during double-strand DNA break repair and immunoglobulin class-switch recombination (CSR) have been unveiled. Nevertheless, given the decreased all classes of immunoglobulins in most patients, CSR deficiency alone cannot fully account for the immunodeficiency. The latest finding showing dysregulation of immunoglobulin signaling may provide a clue to understanding the immunodeficiency mechanism. While less common, a subgroup of patients exhibits T-cell abnormalities alongside B-cell anomalies, including reduced regulatory T-cells and increased effector memory T-and follicular helper T-cells. The dysregulation of immunoglobulin signaling in B-cells, the imbalance in T-cell subsets, and/or satellite RNA-mediated activation of innate immune response potentially explain autoimmune manifestations in a subset of patients. These findings emphasize the pivotal roles of ICF-related proteins in both B-and T-cell functions. ICF syndrome studies have illuminated many fundamental mechanisms. Further investigations will certainly continue to unveil additional mechanisms and their interplay.